Polymerization increasing the capacitive charge storage for better rate performance: A case study of electrodes in aqueous sodium‐ion capacitors. Issue 4 (23rd September 2022) - Gu, Chengjun; Liu, Zhihao; Gao, Xiang; Zhang, Qi; Zhang, Zhanhui; Liu, Zhitian; Wang, Chengliang
Abstract: Organic molecules and polymers have been widely used in aqueous sodium‐ion capacitors. However, the difference in the reaction kinetics of the electroactive polymer and its monomer has been overlooked. In this study, a comparative study of the sodium‐ion storage performance and the reaction kinetics is performed. The poly(perylene diimides) which is named EDP exhibits decreased crystallinity, smaller particle size with a rough surface, higher specific capacitance, lower reduction potential, better cycling stability, and rate performance, compared with its monomer 3, 4, 9, 10‐perylenetetracarboxylic dianhydride. The reaction kinetics study proves that the EDP shows faster sodium‐ion diffusion and more capacitive charge storage, which are responsible for the high‐rate capability. Abstract : The application of poly(perylene diimides) in aqueous sodium‐ion capacitors was reported and exhibited decreased crystallinity, smaller particle size with a rough surface, higher specific capacitance, lower reduction potential, better cycling stability, and rate performance, compared with its monomer 3, 4, 9, 10‐perylenetetracarboxylic dianhydride.